PENDAMPINGAN PERBAIKAN DAN DESAIN KEMASAN PRODUK UKM MAKANAN TRADISIONAL DI KECAMATAN CIPAYUNG JAKARTA TIMUR - Bonitasari Nurul Alfa; Puspita Dewi Widayat; Asmirawati Ismail (Jurusan Teknik Informatika dan Komputer, 2023)
Halal is no longer an attraction, but now it has become an important need. Products that are not kosher will find it difficult to reach a wide market which will ultimately reduce the level of sales. Handling or handling is one of the key elements of the requirements of a product can be said to be halal. If the handling of the product at a stage is not halal, it will affect the subsequent process. Therefore, it is necessary to hold a community service activity that can educate the business community to be able to get to know about handling halal products. The activity of introducing the process of handling halal products to business actors or MSMEs is carried out in the form of webinars. Webinar activities are carried out with the method of delivering material (classical) related to the process of handling halal products for MSME actors and group discussion activities. In the material on the halal material handling process, several points were conveyed, namely the product storage process, the product distribution process, the product presentation process, and the product handling process did not meet the criteria. Based on the results of the questionnaire, in general, the resource persons were considered capable and could deliver the material well which was shown with a score of 4-5 out of a maximum of 5. Participants who already have a business, are motivated to immediately carry out halal certificate management on the business that has been run.